Feasibility Analysis of a Roof Tile Factory Business Using a Capital Budgeting Approach - Clea Putri, Famelga (PT. SAFARI AMALIA, 2023)
Natural content that supports the need for raw materials and materials needed is provided by the nature around us, such as various plants, soil, water, natural stones, and others. Most of them can be further processed into raw materials for construction products, such as roof tiles and other infrastructure facilities. The financial feasibility aspect is important considering that the business can be categorized as a project, which requires a long payback period based on the accounting period. During this time period there are various things that are full of uncertainty which are influenced by the rate of inflation and bank interest rates, so that the value of investments issued and the income or money obtained now will be different from the value of money in the future, which is called with the value of time rather than money. It is hoped that the analytical tool will be able to provide consideration, input and anticipation for the future of the roof tile manufacturing unit project by paying attention to capital budgeting, which can then be analyzed from a financial aspect through payback period (PP), net present value (NPV), profitability index ( PI) and internal rate of return (IRR). In the roof tile manufacturing business, the PBP is 1 year, 8 months, 6 days faster than the maximum period of 8 years of the project value, positive NPV of IDR 536,821,468, PI of 2,841 greater than number 1 and IRR of 14,835 greater than the cost value of capital 12%. As a basis for decision making through a capital budgeting approach through financial analysis.